NALAR HUKUM PRISMATIK DALAM KONTEKS HUKUM NASIONAL - Akhmad Rudi Maswanto; Ahmad Khoirul Anam (Fakultas Syariah - IAI Al-Qolam Malang, 2021)
Indonesia's rule of law is a combination of the rechtstaat concept and the rule of law. It can be seen from the side of law enforcement that emphasizes the importance of a just law of certainty and the importance of law efficacy. Other criteria state that Indonesian law isa crystallization of the source of pancasila law and the bill 45,combining the good elements of the concept of individualism and communality/collectivism that are accepted by pancasila, where personal rights are part of a feeling of personal ownership in the